2016
DOI: 10.1080/08977194.2016.1199553
|View full text |Cite
|
Sign up to set email alerts
|

In ovo exposure to monochromatic lights affect posthatch muscle growth and satellite cell proliferation of chicks: role of IGF-1

Abstract: To study the role of IGF-1 on stimulation with monochromatic light during incubation altering posthatch muscle growth, chicken embryos were exposed to blue light, green light, red light, white light or darkness throughout embryonic period and then were raised in white light conditions upon hatching. Comparing with the other treatment groups, the chicks in green light group had heavier hatching weights, higher muscle indexes and larger muscle fibers. Both in vivo and in vitro studies showed that the number and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Satellite cells were harvested using a previously published method ; the specific steps are as follows: The eggshell was sterilized with 75% alcohol; the pectoral and gastrocnemius muscles were removed from the embryo under sterile conditions using petri dishes; and the fat, fascia and connective tissue were carefully removed. Muscles were washed with pH 7.4 Hanks balanced salt solution, cut into approximately 1‐mm pieces and then treated with 0.1% collagenase type I (1 g L −1 ; Gibico BRL, Grand Island, NY) at 37°C for 30 min and 0.25% trypsin (Gibico BRL) solution at 37°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite cells were harvested using a previously published method ; the specific steps are as follows: The eggshell was sterilized with 75% alcohol; the pectoral and gastrocnemius muscles were removed from the embryo under sterile conditions using petri dishes; and the fat, fascia and connective tissue were carefully removed. Muscles were washed with pH 7.4 Hanks balanced salt solution, cut into approximately 1‐mm pieces and then treated with 0.1% collagenase type I (1 g L −1 ; Gibico BRL, Grand Island, NY) at 37°C for 30 min and 0.25% trypsin (Gibico BRL) solution at 37°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…After culturing satellite cells for 24 h, we discarded the supernatant, and the cells were washed two times with DMEM. Then, different concentrations of IGF‐1 (Final concentration: 0, 50, 100 and 200 ng mL −1 ; Sigma) were added to the cell culture media, with DMEM in the control wells, as previously published . Satellite cell activity was detected using the MTT assay as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, green light (GL) stimulation has been shown to accelerate muscle growth in broilers [4], and enhance the secretion of insulin-like growth factor I (IGF-I) by chick embryo hepatocytes [5,6]. IGF-I has been shown to be a key regulator of muscle development and metabolism in birds and other vertebrate species [7,8], and promoted satellite cells proliferation through IGF-I signaling [9]. Liu et al [10] have shown that GL illumination promoted chick satellite cell myogenic processes during early posthatch stages, and IGF-I played a central role.…”
Section: Introductionmentioning
confidence: 99%
“…Then light information is converted into the biological signals, which affects the secretion of plasma hormones through the pituitary portal system and regulates the physiological function of the body [3]. Previous studies have found that green light signi cantly elevated liver insulin growth factor-1 (IGF-1) secretion [4], skeletal satellite cells proliferation [5,6], muscle growth [7,8], and improved meat quality in broilers [9,10]. While, the growth hormone [11] plays an important role in promoting the growth and development and improving the productive performance of broilers [12].…”
Section: Introductionmentioning
confidence: 99%